142k views
3 votes
-(3/(2y+12))+2=-(8/(y+6)

1 Answer

2 votes

Answer:

Explanation:

lets start with the OG: -(3/(2y+12))+2=-(8/(y+6))

now what? Lets think about it... We need common denominators to get anywhere so lets do that first.

[-3(2)(2y+12)]/(2y+12)= -8/(y+6)

now we can cross multiply to make it a little easier

-6(2y+12)*(y+6)=(2y+12)(-8)

simplify

-6(2
y^(2)+24y+72)= -16y-96

-12
y^(2) -144y -432 = -16y -96

(all of these are negative so you can just take all the negs out)

12
y^(2) +144y +432 = 16y +96

add common multiples

12
y^(2) +160y +528=0

all of these have a common multiple of 4 so divide all by 4 to simplify before factoring

3
y^(2) +40y +132 = 0

you cant really factor this equation without a calculator so thats all I got... sorry

User Retorquere
by
5.9k points